2008
DOI: 10.1063/1.3010375
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort-pulse laser calligraphy

Abstract: Control of structural modifications inside silica glass by changing the front tilt of an ultrashort pulse is demonstrated, achieving a calligraphic style of laser writing. The phenomena of anisotropic bubble formation at the boundary of an irradiated region and modification transition from microscopic bubbles formation to self-assembled form birefringence are observed, and the physical mechanisms are discussed. The results provide the comprehensive evidence that the light beam with centrosymmetric intensity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 13 publications
4
61
1
Order By: Relevance
“…Finally, we report the observation in laser machining by ps-pulses of the so called "quill effect" whereby laser-matter interaction is shown to be sensitive to the direction of movement of the laser beam [13,26]. A marked sensitivity of the material modification from the direction of writing is observed when 8 ps pulses of 2 μJ pulse energy are focused with a 0.65 NA objective 150 μm below the surface of a silica plate (Fig.…”
Section: Assessment Of Ps-lasers For the Fabrication Of Spatially-varmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we report the observation in laser machining by ps-pulses of the so called "quill effect" whereby laser-matter interaction is shown to be sensitive to the direction of movement of the laser beam [13,26]. A marked sensitivity of the material modification from the direction of writing is observed when 8 ps pulses of 2 μJ pulse energy are focused with a 0.65 NA objective 150 μm below the surface of a silica plate (Fig.…”
Section: Assessment Of Ps-lasers For the Fabrication Of Spatially-varmentioning
confidence: 99%
“…The lines were written 100 μm below the surface by translating the sample transversely to the beam propagation direction. In order to prevent changes in the material modifications by reversal of the writing direction, all lines were written in the same direction [13]. Laser inscription was carried out aligning the direction of the light polarization both orthogonal and parallel to the writing direction using a half-wave plate placed immediately before the focusing lens.…”
Section: Experimental Set-up and Methodsmentioning
confidence: 99%
“…Note the transition form smooth (uniform) WG to a self-arranged quasi-periodical structure for forward translation direction only. These effects can be explained by slight tilting of the phase wavefront, which most likely originate from the micro-objective misalignment but not from the compressor, as for example was stated in the [20]. The reconstructed RI distributions are plotted on Fig.…”
Section: Refractive Index Visualisation and Reconstructionmentioning
confidence: 99%
“…More recently, we have experimentally demonstrated that indeed the pulse front tilt [5] can be used as a new tool material modification control and optical manipulation, e.g. for achieving calligraphicstyle laser writing, when the appearance of a "stroke" varies in relation to its direction [6].It has also been a common belief that in a homogeneous medium, the photosensitivity and corresponding light-induced material modifications do not change on the reversal of light propagation direction. Recently, we have demonstrated that when the direction of the femtosecond laser beam is reversed from +Z to -Z directions, the structures written in a lithium niobate crystal are mirror images when translating the beam along the +Y and -Y directions (Fig.…”
mentioning
confidence: 97%
“…More recently, we have experimentally demonstrated that indeed the pulse front tilt [5] can be used as a new tool material modification control and optical manipulation, e.g. for achieving calligraphicstyle laser writing, when the appearance of a "stroke" varies in relation to its direction [6].…”
Section: Introductionmentioning
confidence: 99%